Experiential learning for agricultural students in institutions of higher learning: The case of Egerton University - Mungai, N. M.; AMBULA, M.; CHEGE, N.W.; MBERIA, P.; OMBAT, M.J.; OPIYO, M.A.; BEBE, O.B.; AYUYA, I.O.; WAMBUA, T. (My University, 2016)
Traditionally, many universities have majored in training and research but are increasingly under pressure to proactively engage communities through their academic programmes. The need to produce graduates with practical experience in their areas of specialization is real and urgent. Universities must therefore seek innovative approaches to provide students with experiential learning through internship programmes, among other approaches. This paper documents Egerton University’s farm attachment programme that provides agricultural students an opportunity to work with rural communities as part of their training. The paper outlines the approach used, characteristics of farms and farmers that participated in the programme, typology of students participating, lessons learnt and the impacts of the programme. Students were attached on farms for a minimum of eight weeks where they spent 3-4 days in the farm and 1-2 days at the SubCounty Agricultural offices. Since January 2014 when the programme was initiated, over 200 students and about 100 farmers have participated in the programme. Impacts and benefits of the programme include increased productivity at the farm level, increased awareness and utilization of agricultural technologies by farmers and students, lessons and experiences pointing to the need for curriculum review, as well as need for prompt, reliable and unbiased agricultural information, and ethnic integration. Integration of the farm attachment programme experiences into university-wide learning and teaching curricula and/ or approaches will go a long way in safeguarding benefits realized and thus, increasing the relevance and contribution by Egerton University to development agenda . A model for scaling up the programme for greater impact is discussed.
Keywords: Academic programmes; farm attachment; undergraduate students; universities